2016
DOI: 10.1080/15384047.2016.1139244
|View full text |Cite
|
Sign up to set email alerts
|

Role of miR-27a, miR-181a and miR-20b in gastric cancer hypoxia-induced chemoresistance

Abstract: Despite the search for new therapeutic strategies for gastric cancer (GC), there is much evidence of progression due to resistance to chemotherapy. Multidrug resistance (MDR) is the ability of cancer cells to survive after exposure to chemotherapeutic agents. The involvement of miRNAs in the development of MDR has been well described but miRNAs able to modulate the sensitivity to chemotherapy by regulating hypoxia signaling pathways have not yet been fully addressed in GC. Our aim was to analyze miR-20b, miR-2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
55
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 65 publications
(57 citation statements)
references
References 39 publications
2
55
0
Order By: Relevance
“…In the present study we observed reduced miR-20b expression levels in Ishikawa cells under hypoxic conditions. These data are in line with aforementioned reports of Lei et al as well as of Danza et al in gastric cancer (85,86).…”
Section: Discussionsupporting
confidence: 83%
“…In the present study we observed reduced miR-20b expression levels in Ishikawa cells under hypoxic conditions. These data are in line with aforementioned reports of Lei et al as well as of Danza et al in gastric cancer (85,86).…”
Section: Discussionsupporting
confidence: 83%
“…According to previous studies, lncRNA could act as a specific "Sponge" of miRNA to reduce their regulatory effect on mRNAs [Paraskevopoulou and Hatzigeorgiou, 2016]. Given the important role of miR-181a in regulating growth, invasion and chemo-resistance of many kinds of cancer [Danza et al, 2016;Xu et al, 2016], we validated whether CASC2 sensitize glioma cells to TMZ through miR-181a. As shown by real-time PCR, CASC2 could reduce the detectable amount of miR-181a, while up-regulating miR-181a expression could reduce CASC2 expression, indicating that miR-181a exerted similar regulatory behaviors as CASC siRNAs, so we speculated that miR-181a may regulate CASC expression via the RNAi pathway at the post-transcriptional level.…”
Section: Discussionmentioning
confidence: 98%
“…Recent work reported that miR‐181a plays an oncogenic role in several cancers through promoting cancer cell proliferation, invasion, migration, as well as chemo‐resistance [Galluzzi et al, ; Zhai et al, ; Danza et al, ; Zhao et al, ]. Song et al revealed that inhibition of microRNA‐181a may suppress proliferation and invasion and promote apoptosis of cervical cancer cells through the PTEN/Akt/FOXO1 pathway [Xu et al, ].…”
Section: Discussionmentioning
confidence: 99%
“…Also, miR-26 is induced in response to low oxygen and decreases proapoptotic signaling in a hypoxic environment [40], while miR-122-5p inhibition attenuates hypoxia/reoxygenation-induced myocardial cell apoptosis by targeting GATA4 [41]. There is also evidence showing that miR-145-5p is downregulated by ischaemia in acute myocardial infarction via targeting Dab2 [42] and miR-181a-5p is involved in hypoxia-induced chemoresistance in gastric cancer [43]. Other studies showed that miR-34a-5p, miR-182, and miR-146a-5p were the three downregulated miRNAs upon hypoxia and miR-34a-5p inhibition protects against anoxia/reoxygenation injury in cardiomyocytes in vitro [44, 45].…”
Section: Discussionmentioning
confidence: 99%